Recompression Improves Release Success in Pollack ( Pollachius pollachius ): A Step Towards Assessing Post Release Mortality in a Recreational Fishery - T. Stamp; R. Mawer; R. Conlon; A. E. Hall; P. Davies; R. Nesbit; D. Uren; T. Morris; S. Sullivan; S. Thomas; B. D. Stewart; H. Rudd; et al. (Fisheries Management and Ecology, 2026)
The recreational fishery for pollack ( Pollachius pollachius ) in the northeast Atlantic is impacted by the species' high sensitivity to barotrauma. When captured at depth and brought to the surface, gas expansion within the peritoneal cavity can cause a variety of injuries and hinder release. Via an experimental weighted cage, this study evaluated the efficacy of releasing Pollack at depth as a barotrauma mitigation strategy. We found that depth‐release significantly increased the probability of released Pollack displaying an active escape response to 83%, compared to 56% for surface‐released fish; however, increased capture depth and fish size negatively affected success. Camera observations of depth‐released Pollack confirmed the recovery of vital reflexes (vestibulo‐ocular reflex, equilibrium maintenance) within 1.5–4 min. Further acoustic telemetry demonstrated that individuals subsequently displayed active dispersion from the release site (0.1–23.8 km) and showed active vertical movements for up to 6 months post‐release. These findings indicate that depth‐release improves survival outcomes, though further research is required to optimise release methods in open‐water environments.